Notch and interacting signalling pathways in cardiac development, disease, and regeneration. Issue 11 (November 2018) - MacGrogan, Donal; Münch, Juliane; de la Pompa, José
Abstract Cardiogenesis is a complex developmental process involving multiple overlapping stages of cell fate specification, proliferation, differentiation, and morphogenesis. Precise spatiotemporal coordination between the different cardiogenic processes is ensured by intercellular signalling crosstalk and tissue–tissue interactions. Notch is an intercellular signalling pathway crucial for cell fate decisions during multicellular organismal development and is aptly positioned to coordinate the complex signalling crosstalk required for progressive cell lineage restriction during cardiogenesis. In this Review, we describe the role of Notch signalling and the crosstalk with other signalling pathways during the differentiation and patterning of the different cardiac tissues and in cardiac valve and ventricular chamber development. We examine how perturbation of Notch signalling activity is linked to congenital heart diseases affecting the neonate and adult, and discuss studies that shed light on the role of Notch signalling in heart regeneration and repair after injury. In this Review, de la Pompa and colleagues describe the role of the Notch pathway during the differentiation and patterning of cardiac tissues and in valve and ventricular chamber development, discussing the crosstalk with other signalling pathways, how defective Notch signalling is linked to congenital heart diseases, and the relevance of the Notch pathway in heart regeneration and repair. Key points Vertebrate heart development is a complex multistep process that relies on the contribution of several cellular lineages in a spatiotemporally regulated manner. Notch is a highly conserved, local cell–cell signalling pathway required for proliferation, differentiation, and tissue patterning in a variety of tissues, including the heart. Notch signalling in the endocardium regulates cardiac specification, progenitor cell differentiation, valve primordium formation and morphogenesis, ventricular trabeculation and compaction, and coronary vessel development. Notch coordinates cellular interactions during heart development by cross talking with other fundamental signalling pathways, including WNT, bone morphogenetic protein, and neuregulin 1–ERBB. Defective Notch signalling during heart development causes congenital heart disease affecting neonates and adults. Notch regulates cardiac regenerative processes in zebrafish, providing an incentive for evaluating Notch-based cell therapies in humans.